Una Costa Rica que debemos conocer - Bedoya, Eduardo (2013)
This article deals with the maritime boundaries of Costa Rica and eventually with its future territory once all negotiations and approved on this subject have conclude. It shows original measurements of different types of maritime areas, which correspond to the Pacific ocean and the Caribbean sea, as well as that of the Coco island.